Genomic Landscape of Divergence in Ballan Wrasse ( Labrus bergylta ) - Eeva Jansson; Fernando Ayllon; Carl‐Johan Rubin; Laura Casas; Fran Saborido‐Rey; Tomasz Furmanek; Marine S. O. Brieuc; David Villegas‐Rios; María Quintela; Rolf B. Edvardsen; Roger Lille‐Langøy; Kevin A. Glover (Molecular Ecology, 2025)
The architecture underpinning genomic divergence is still a largely uncharted territory and likely case‐dependent. Here, we investigated genome‐wide variation in Ballan wrasse, a northeastern Atlantic fish species that displays two sympatric colour morphs, spotty and plain, that have been suggested to represent subspecies. We produced a chromosome‐level reference genome and thereafter investigated genomic divergence among 152 individuals including both morphs, from two localities in Spain and Norway each and one in France. Differences between morphs dominated in Spain in accordance with sympatric divergence, whereas in Norway allopatric differentiation was prominent and repeated genomic signals of local divergence were found. Chromosomes had large low‐recombining areas shared across all populations. Within the Spanish morphs, these areas contained large islands of divergence, totalling ~11% of the genome, and showed high morph specificity and strong selection. The same regions showed frequent admixture in the French morphs and no differentiation in Norway. In contrast, divergent regions observed between sampling localities in Norway were shorter and found throughout the genome. High inbreeding and lower diversity were observed in the Norwegian samples, consistent with the proposed recolonisation bottleneck and subsequent drift. Several genomic regions were significantly associated with morphs and contained tens of genes of diverse functions, suggesting that colouration is unlikely to be the sole driver of divergence. Our results do not support the hypothesis of shared larger genomic features underlying intraspecific colour divergence. Instead, we observe gradual accumulation of differences into low‐recombining regions, likely when additional factors like assortative mating and/or lack of gene flow favour their development.

Editorial: Prospects and challenges for the implementation of HTS genetic methods in fisheries research surveys and stock assessments - Laura Casas; Reinhold Hanel; Francesc Piferrer; Fran Saborido-Rey (Frontiers in Marine Science, 2023)

A review of an emerging tool to estimate population parameters: the close-kin mark-recapture method - Laura Casas; Fran Saborido-Rey (Frontiers in Marine Science, 2023)
Knowing the number of individuals in a population is fundamental for the sustainable management of exploited marine resources but estimating this parameter is often extremely challenging, especially in large, highly mobile and dispersed populations. Abundance estimation traditionally relies on multiple data types that include the relationship between fishery catches and effort (Catch Per Unit Effort or CPUE), scientific research surveys and demographic models that are developed to estimate past and current stock dynamics, but uncertainty is often high. Close-kin mark-recapture (CKMR) is an alternative method for estimating abundance and other demographic parameters (e.g. population trend, survival rates, connectivity), using kinship relationships determined from genetic samples. This methodology is based on a simple concept - the larger the population the less likely to find relatives and vice versa - and was proposed two decades ago although regained considerable attention recently. Refinements in the statistical methodology and advances in high throughput sequencing methods have boosted the efficiency of genomic analysis, promising to revolutionize the field of fisheries stock assessments. In theory, it can be applied to almost any species, provided that there is sufficient information about the life-history/biology of the organism and that the populations are not so small as to be almost extinct or so large that finding relatives becomes extremely difficult. Thus, it has the potential to provide baseline data for the many exploited fish stocks that remain largely unassessed and to reduce uncertainty in those that are regularly evaluated. Here, we provide an overview of the method in the context of fisheries assessments, analyze the advances and synthetize the field studies published in the last five years. Moreover, we evaluate the readiness, viability and maturity of the method to infer demographic parameters in species spanning diverse life histories. We evaluate technical considerations and requirements for a successful application and analyze the main challenges and limitations preventing a broader implementation.

A review of genomics methods and bioinformatics tools for the analysis of close-kin mark-recapture - Laura Casas; Fran Saborido-Rey (Frontiers in Marine Science, 2023)
Stock assessments serve to monitor the condition of fish stocks and exploit them sustainably but require accurate data such as growth and mortality rates as input parameters. Most species fished worldwide lack the data needed to assess their status and even those closely assessed are often based on parameters that are known to contain uncertainty. This has resulted in an increased share of overfished stocks over the last half century, demanding urgently innovative methodologies that can provide novel means to reduce uncertainty of fish stocks assessments and expand the range of assessed species. CKMR has emerged recently attracting a great interest due to its potential to provide accurate demographic parameters of interest in stock assessments. The method is at the crossroads between fisheries science and genomics, requiring specialized knowledge that is usually outside of the experience of fisheries scientist and modellers, complicating the application of the method and its uptake in regular fisheries assessments. In this review, we provide useful information to perform the genomics and bioinformatics steps required to complete successfully a CKMR study. We discuss the most suitable genomics assays, considering the amount of information they provide, their easiness of use and cost of genotyping accurately the large number of individuals needed to assess most fish stocks. We provide an overview of methods of analysis and statistical methodologies that can be used to infer kinship with the accuracy required in a large population setting with sparse sampling, where most individuals are unrelated, determining a low probability of finding closely related individuals. We analyse potential sources of biases and errors and provide recommendations to facilitate the application of CKMR to a wider range of fish stocks.

The potential use of genomic methods in bottom trawl surveys to improve stock assessments in Europe - Rebeca Rodríguez-Mendoza; Fran Saborido-Rey (Frontiers in Marine Science, 2023)
In Europe, research surveys carried out by state governments provide the great majority of fishery-independent data. Member States (MS) in the European Union (EU) regularly conduct research surveys to provide the necessary data to assess the status of exploited fish stocks and to monitor the general condition of the marine ecosystem. In the surveys, samplings are carried out throughout the distribution range of the targeted fish species using standardized gears (e.g., trawls and seines) and other methods (e.g., hydroacoustics and underwater cameras). In the context of fish stock assessment, survey data are important because they provide indices that help tuning the stock assessment models (e.g., the index of fish abundance) and key information about the size and age distributions of the stock, the size-age relationships, the proportion of fish mature at each age, and information on reproductive performance of the stocks. However, research surveys have a number of shortcomings that include, for example, a high economic cost coupled with complex logistics and a long time required for processing the collected data. In addition, some of the parameters that are needed in stock assessment cannot be estimated from survey data for certain commercially important species. For instance, age is usually determined using hard structures (such as otoliths) in fish target species. However, for European hake, age cannot be determined accurately because there are many difficulties in interpreting the ring patterns of the otoliths. This highlights the need to look for alternative methodologies such as genomics, that have the potential of improving the data obtained from research surveys and hence, improve fish stock assessments. Considering this, we carried out a review of the bottom trawl research surveys in the EU with the purpose of: 1) identifying the current approaches for monitoring fishery resources and the ecosystem and 2) determining how genomic techniques can be used to improve survey data, taking into account the needs of current and future stock assessment in Europe.

State-of-the-art of data analyses in environmental DNA approaches towards its applicability to sustainable fisheries management - Natalia Petit-Marty; Laura Casas; Fran Saborido-Rey (Frontiers in Marine Science, 2023)
An increasing number of studies using marine environmental DNA (eDNA) approaches are showing its potential application in marine fisheries management by helping and simplifying some of the labor-intensive traditional surveys required to assess exploited populations and ecosystem status. eDNA approaches (i.e. metabarcoding and targeted) can support to ecosystem-based fisheries management by providing information on species composition; surveillance of invasive, rare and/or endangered species; and providing estimates of species abundance. Due to these potential uses in fisheries and conservation sciences, the number of studies applying eDNA approaches in marine habitats has expanded in the very last few years. However, a lack of consistency across studies when applying pipelines for data analyses, makes results difficult to compare among them. Such lack of consistency is partially caused by poor knowledge in the management of raw sequences data, and analytical methods allowing comparative results. Hence, we review here the essential steps of eDNA data processing and analyses to get sound, reproducible, and comparable results, providing a set of bioinformatics tools useful for each step. Altogether this review presents the state of the art of eDNA data analyses towards a comprehensive application in fisheries management promoting sustainability.

Shifts in the seasonal trophic ecology of larvae and juveniles of European hake ( Merluccius merluccius ): From the Galician upwelling system (NW Spain) - Raúl Laiz‐Carrión; Águeda Cabrero; José María Quintanilla; Alma Hernández; Amaya Uriarte; Jesús Gago; José María Rodríguez; Carmen Piñeiro; Alberto García; Fran Saborido‐Rey (Fisheries Oceanography, 2022)
The trophic ecology of European hake ( Merluccius merluccius ) larvae and early‐juveniles from the Iberian shelf off Galicia (NW Spain) are assessed by means of stable isotopes (SIA) and nutritional condition in conjunction with hydrobiological variations observed during the winter and summer season of 2012. Hake early‐juveniles (18–47 mm SL) showed higher δ 15 N than larvae (3–11 mm SL) together with the microzooplankton (55–200 μm) and mesozooplankton (>200 μm) during both seasons. Low δ 15 N values and high variability in both zooplankton and hake larvae were found during winter coinciding with an unusually strong upwelling event. Inversely, high δ 15 N content in zooplankton in summer suggests strong nitrogen reutilization. However, hake larvae sampled in summer had a higher RNA:DNA ratio in line with higher Fulton condition factors than those sampled in winter. Higher δ 13 C values for microzooplankton and mesozooplankton and hake larvae in summer compared to late winter point to prey availability differences. The relationship between nitrogen and carbon stable isotopes versus size or weight suggests an ontogenetic shift in the diet of hake larvae. Early‐juveniles had a lower isotopic niche width compared to larvae in both late winter and summer, indicating a trophic specialization related to changes following settlement process from planktonic life to demersal habitat. Higher trophic specialization was observed in summer, which recorded a narrower isotopic niche and higher trophic position estimations.

The Use of Daily Growth to Analyze Individual Spawning Dynamics in an Asynchronous Population: The Case of the European Hake from the Southern Stock - Cristina García-Fernández; Rosario Domínguez-Petit; Fran Saborido-Rey (Fishes, 2022)
Daily growth patterns and their relationship with reproduction was analyzed in the European hake from the Galician Shelf, where it shows a very protracted spawning with three spawning peaks. The daily growth analysis was performed in otoliths of adult females on the transversal section of the sagittae otolith. Daily increments were measured from the border to the nucleus in females until they were discernible. Results show that daily growth of females decreases during the spawning period because they allocate less energy to somatic growth in favor of the production of gametes, with an increase in growth in July. Lastly, daily growth individual trends showed a “spawning pattern” in 28% of medium and large females, suggesting an individual spawning period of one to two months, with 4–5 valleys of narrow daily increments, likely associated to batch release: individual spawning frequency would be 4–5 days. This is the first time that individual spawning frequency in hake is estimated based on individual data. Finally, the spawning pattern is detected only once per year, indicating that a single female participates only in one spawning peak per year, supporting the hypothesis of the existence of two or more spawning components in the stock.

Atlantic Cod Growth History in Flemish Cap Between 1981 and 2016: The Impact of Fishing and Climate on Growth Performance - Raquel Ruiz-Díaz; Rosario Dominguez-Petit; Fran Saborido-Rey (Frontiers in Marine Science, 2022)
Flemish Cap cod collapsed in the early 90’s after facing multiple threats due to climate variability and anthropogenic pressures. A master 35-year cod growth chronology was reconstructed in the present study by using sclerochronology techniques. Three additional chronologies were developed to account for the age-dependent effect of maturity and fishing intensity on growth. All chronologies showed that cod growth has decreased over the years and it is currently at the minimum level in the historic of data series. Hierarchical mixed-effects models were applied to the master chronology to identify extrinsic drivers of growth. The master chronology was divided into 3 periods: Premoratorium (1988-1998), Moratorium (1999-2009), and Postmoratorium (2010-2019). Our results showed that drivers of cod growth in the Flemish Cap varied between periods (Premoratorium: bottom temperature and fishing mortality, Moratorium: cod and pandalus abundance, and Postmoratorium: cod abundance and thickness of the cold intermediate layer). Our results suggest that density-dependence processes, food availability, and global warming may be behind the lack of recovery of the Flemish Cap cod stock. The Flemish Cap cod growth chronology shows variations on growth over time and identifies its drivers, having the potential to be included in the NAFO stock assessments or to be used to set dynamic reference points that guarantees the stock sustainability.

Spatial and Temporal Variability in the Occurrence and Abundance of European Hake Larvae, Merluccius merluccius, on the Galician Shelf (NE Atlantic) - Cristina García-Fernández; Justin J. Suca; Joel K. Llopiz; Paula Álvarez; Rosario Domínguez-Petit; Fran Saborido-Rey (Frontiers in Marine Science, 2021)
The European hake ( Merluccius merluccius ) is represented as one of the most valuable fisheries in the Galician shelf. We analyzed the distribution, abundance, and environmental conditions of the southern-stock European hake larvae from the Galician shelf during the two main spawning peaks, winter-spring and summer, based on the data from three ichthyoplankton surveys (March 2012, March 2017, and June 2017). A total of 395 larvae in March 2012, 121 in March 2017, and 69 in June 2017 were captured. The northeast section of the study area, close to Estaca de Bares, primarily between 100 and 200 m isobaths, had the highest presence of the European hake larvae in all surveys. Generalized additive models (GAMs) indicated that the occurrence of larvae was significantly different between the surveys and was associated negatively with the temperature, while the abundance of larvae was significantly different between sampling years and was the highest at a temperature around 13.36°C and at sea surface heights of about −0.48 m. Studies of the distribution of early life stages and their relation to external conditions are essential to the understanding of the complex process of recruitment, especially in the exploited species and in highly dynamic environments like the Galician shelf.

Larval Fish Community in the Northwestern Iberian Upwelling System during the Summer Period - Sonia Rábade Uberos; Alba Ruth Vergara Castaño; Rosario Domínguez-Petit; Fran Saborido-Rey (Oceans, 2021)
The Galician shelf (northwestern Iberian Peninsula) is a highly dynamic area with an important multi-species fisheries industry that exploits resources from several habitats, characterized by being not only highly diverse, rich, and productive but also seasonally and interannually variable. Early life stages of different species are distributed throughout the year, with fluctuating abundances and community composition. Likewise, the influence of environmental factors and processes on larval production and survival remains unknown. Sampling was carried out in July 2012, and all the larvae obtained were identified to establish the specific composition of the community in a summer upwelling scenario. The results show no zonation in the species distribution, a consequence of the mixing effects of the upwelling and eddies, with high diversity but low abundance, which render in a slight predominance of a few species. Due to the dependence of planktonic populations on upwelling events, which was not highly pronounced in 2012, we cannot conclude that this was a typical conformation of the Galician summer larval fish community, but it is a first approach to comprehend the community composition.

Genomic landscape of geographically structured colour polymorphism in a temperate marine fish - Laura Casas; Pablo Saenz‐Agudelo; David Villegas‐Ríos; Xabier Irigoien; Fran Saborido‐Rey (Molecular Ecology, 2021)
The study of phenotypic variation patterns among populations is fundamental to elucidate the drivers of evolutionary processes. Empirical evidence that supports ongoing genetic divergence associated with phenotypic variation remains very limited for marine species where larval dispersal is a common homogenizing force. We present a genome‐wide analysis of a marine fish, Labrus bergylta , comprising 144 samples distributed from Norway to Spain, a large geographical area that harbours a gradient of phenotypic differentiation. We analysed 39,602 biallelic single nucleotide polymorphisms and found a clear latitudinal gradient of genomic differentiation strongly correlated with the variation in phenotypic morph frequencies observed across the North Atlantic. We also detected a strong association between the latitude and the number of loci that appear to be under divergent selection, which increased with differences in coloration but not with overall genetic differentiation. Our results demonstrate that strong reproductive isolation is occurring between sympatric colour morphs of L . bergylta found at the southern areas and provide important new insights into the genomic changes shaping early stages of differentiation that might precede speciation with gene flow.

Spatio-Temporal Assessment of the European Hake (Merluccius merluccius) Recruits in the Northern Iberian Peninsula - Francisco Izquierdo; Iosu Paradinas; Santiago Cerviño; David Conesa; Alexandre Alonso-Fernández; Francisco Velasco; Izaskun Preciado; Antonio Punzón; Fran Saborido-Rey; Maria Grazia Pennino (Frontiers in Marine Science, 2021)
The protection of fish nurseries has been recognized as a useful tool to efficiently manage fisheries given that protected areas enhance the recruitment of target species. To identify and locate potential nursery areas, a solid understanding of species-environment relationships and their spatio-temporal dynamics is needed. Within this context, in this study we assess where European hake ( Merluccius merluccius ) recruits persistently aggregate in the northern continental shelf of the Iberian Peninsula. Hake recruit data collected during scientific trawl surveys between 2005 and 2016 were analyzed using Bayesian hurdle hierarchical spatio-temporal models, considering the environmental variables bathymetry, sea bottom temperature and salinity. Additionally, three different spatio-temporal structures (i.e., persistent, progressive, or opportunistic) were compared to assess the temporal persistence of nurseries over time. Among all the environmental variables analyzed, bathymetry was the most important. The preferential habitat of recruits was found to be within a bathymetric range of 120–200 m. Our findings clearly show that there is a temporally persistent main nursery located along the continental shelf of the Artabrian gulf (off La Coruña) in addition to several areas with high aggregations of hake recruits but with strong inter-annual variability. We argue that the analytical framework applied in this study allowed us to identify European hake nurseries in the northern continental shelf of the Iberian Peninsula, as well as their spatio-temporal fluctuations throughout the study period (2005–2016), and to assess which environmental factors, among bathymetry, sea bottom temperature and salinity, influence the occurrence and abundance of recruits in the study area. Results of our models also produce a new abundance index that could be useful for improving traditional stock assessment models.

Size-dependent change in body shape and its possible ecological role in the Patagonian squid (Doryteuthis gahi) in the Southwest Atlantic - Jessica B. Jones; Graham J. Pierce; Fran Saborido-Rey; Paul Brickle; Frithjof C. Kuepper; Zhanna N. Shcherbich; Alexander I. Arkhipkin (Marine Biology, 2019)

Erratum to: Reproductive tactics of the freshwater fish Brycon guatemalensis (Teleostei: characidae) in the lake Nicaragua - Aldo Hernández-Portocarrero; Rosario Domínguez-Petit; Fran Saborido-Rey (Environmental Biology of Fishes, 2015)

Ontogenetic allometry of the bluemouth, Helicolenus dactylopterus dactylopterus (Teleostei: Scorpaenidae), in the Northeast Atlantic and Mediterranean based on geometric morphometrics - Rebeca Rodríguez-Mendoza; Marta Muñoz; Fran Saborido-Rey (Hydrobiologia, 2011)

Using body geometric morphometrics to identify bluemouth, Helicolenus dactylopterus (Delaroche, 1809) populations in the Northeastern Atlantic - Vera Sequeira; Rebeca Rodríguez-Mendoza; Ana Neves; Rafaela Paiva; Fran Saborido-Rey; Leonel Serrano Gordo (Hydrobiologia, 2011)

Review of the population structure and ecology of S. mentella in the Irminger sea and adjacent waters - Fran Saborido-Rey; Dolores Garabana; Christoph Stransky; Sergey Melnikov; Vladimir Shibanov (Reviews in Fish Biology and Fisheries, 2004)